Menemukan Solusi Inovatif Pengembangan Bahan Ajar dan Media Biologi Berbasis Information and Communication Technologies (ICT) Dalam Pembelajaran - Zebua, Nofamataro; Zebua, Ester Novi Kurnia; Duha, Markus; Zagoto, Jerry Samuel; Sisokhi, Dorotea Trivina; Ndruru, Dedi Yusman (Jurnal Biogenerasi, 2024)
The importance of improving the quality of learning as a response to low student participation and learning outcomes is a major concern in education. One of the efforts made is the need for technology empowerment in classroom learning and the commitment of the teacher concerned. This research uses the literature study method to identify the availability of ICT-based teaching materials in schools. The findings show that the availability of ICT-based teaching materials is still limited, this is due to the uneven infrastructure and the lack of teacher competence in developing teaching materials. Therefore, teacher creativity is needed in utilizing technology in learning activities, especially in developing ICT-based teaching materials and learning media.